Penanggulangan Kriminal Oleh Pemkot Surabaya Melalui Pendekatan Teori Disorganisasi Sosial (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Surabaya is a prototype with industrialization in the growth of the city. In such an environment, crime occurs due to the pressure of forces that divide society, causing social bonds to break and resulting in higher crime rates. Theories of crime in the context of social disorganization discuss the social and spatial structure of a community and how these factors can influence criminal behavior. These theories assume that poor social organization, low socioeconomic status, weak social ties, and high spatial mobility can lead to a lack of social control, which in turn can encourage criminal behavior. The crime theories in the context of social disorganization, particularly the theory developed by Shaw and McKay, focus on how the social and spatial structure of a community can affect criminal behavior. This study was conducted in Surabaya, which is undergoing social changes due to environmental factors, poverty, ethnic wealth, educational status, and an underdeveloped per capita welfare. Data was obtained through surveys and interviews with local residents, as well as statistical analysis related to crime rates. The research findings show that areas with higher levels of social disintegration tend to have higher crime rates. Factors such as unemployment, economic inequality, and weakening social ties have been found to significantly contribute to the increase in crime. In conclusion, social disintegration is a key factor that drives individuals to engage in criminal acts, especially in societies experiencing socio-economic inequalities. Therefore, crime prevention efforts require a comprehensive approach, including strengthening social and economic structures in society through the city government.